Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For the following complex polynomial: Write the following polynomials in Taylor form centered at $z=2$: $z^{10}$

How come this simplifies to just a Taylor series of a binomial?

Detailed explanation will be greatly appreciated!

share|improve this question
    
@5PM $p(x) = z^{10}$ is a Maclaurin series, i.e. about point 0. TS asks about point 2. –  Kaster Feb 11 '13 at 3:46
1  
@Kaster OK. The part "centred at z=2" was not there when I commented. –  user53153 Feb 11 '13 at 3:47

3 Answers 3

up vote 2 down vote accepted

$$ f(z) = f(z_0) + f'(z_0)(z - z_0) + \frac 12 f''(z_0)(z - z_0)^2 + \ldots $$ or otherwise $$ f(z) = \sum_{n = 0}^\infty \frac {f^{(n)}(z_0)}{n!} (z - z_0)^k $$ Obviously, $f^{(n)}(z_0) = 0$ for all $n > 10$ so you end up with $$ f(z) = \sum_{n = 0}^{10} \frac {f^{(n)}(z_0)}{n!} (z - z_0)^k $$ Next, $f^{(n)}(z) = \frac{10!}{(10-n)!}z^{10-n}$, so $$ f(z) = \sum_0^{10} \frac {10!}{(10-n)!n!}z_0^{10-n} (z - z_0)^n $$ which is binomial decomposition for $[z_0 - (z - z_0)]^{10}$, and it makes sense.

PS: here $z_0 = 2$

share|improve this answer

On one hand, if $f(z)=z^{10}$, then $f(z)=a_0+a_1(z-2)+a_2(z-2)^2+\cdots +a_{10}(z-2)^{10}$, with $a_k=\dfrac{f^{(k)}(2)}{k!}$. All higher order terms vanish because $f^{(11)}(z)\equiv 0$. You can directly compute $f^{(k)}(2)$ for $k\in\{0,1,\ldots,10\}$.

On the other hand, $f(z)=z^{10}=(2+(z-2))^{10}=\sum\limits_{k=0}^{10}{10\choose k}2^{10-k}(z-2)^k$ by the binomial theorem.

The fact that these expansions are identical is a consequence of the uniqueness of Taylor series coefficients, but it is also straightforward to verify by induction, without reference to the series, that $f^{(k)}(z)=k!{10\choose k}z^{10-k}=\dfrac{10!}{(10-k)!}z^{10-k}$ for each $k\in \{0,1,\ldots,10\}$ and $z\in\mathbb C$.

share|improve this answer

Another way to look at it is that $z^{10}=((z-2)+2)^{10}$ which is of the form $(a+b)^{10}$ and then just expand using your favorite method of obtaining the binomial coefficients. Since this is a finite binomial expansion it converges for all (complex) numbers.

share|improve this answer
    
Wasn't this way also mentioned in the previous answers? –  Jonas Meyer Feb 11 '13 at 15:35
    
Not in so many words. Just stated it plainly and simply. –  Fixed Point Feb 12 '13 at 8:33

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.